2020
DOI: 10.1016/j.ejogrb.2020.04.065
|View full text |Cite
|
Sign up to set email alerts
|

How to reduce the potential risk of vertical transmission of SARS-CoV-2 during vaginal delivery?

Abstract: The risk of vertical transmission during vaginal delivery in COVID-19 pregnant patients is currently a topic of debate. Obstetric norms on vaginal birth assistance to reduce the potential risk of perinatal infection should be promoted by ensuring that the risk of contamination from maternal anus and faecal material is reduced during vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0
10

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 24 publications
0
40
0
10
Order By: Relevance
“…The PRIORITY study, which included 179 infants born to COVID-positive mothers and 84 infants born to COVID-negative mothers, found no increased risk of preterm birth, NICU admission, and respiratory disease in the COVID-positive cohort, although NICU admission and preterm birth were increased in the sub-group of mothers testing positive 0–14 days before delivery [ 2 , 4 , [8] , [9] , [10] , [11] , [13] , [14] , [15] , 18 , [24] , [25] , [26] ]. The largest cohort study to date followed the courses of 242 COVID-19 positive pregnant women and their 248 infants through the third trimester of pregnancy and one month postpartum [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The PRIORITY study, which included 179 infants born to COVID-positive mothers and 84 infants born to COVID-negative mothers, found no increased risk of preterm birth, NICU admission, and respiratory disease in the COVID-positive cohort, although NICU admission and preterm birth were increased in the sub-group of mothers testing positive 0–14 days before delivery [ 2 , 4 , [8] , [9] , [10] , [11] , [13] , [14] , [15] , 18 , [24] , [25] , [26] ]. The largest cohort study to date followed the courses of 242 COVID-19 positive pregnant women and their 248 infants through the third trimester of pregnancy and one month postpartum [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 40% were early preterm deliveries (occurring between 24 weeks and 33 weeks 6 days gestation), and 60% were late preterm deliveries (occurring between 34 weeks and 36 weeks 6 days gestation) [ 11 ]. Rates of caesarean delivery are extremely high in COVID-19 patients in this meta-analysis, with reported rates of nearly 85% [ 25 , 26 ]. Notably, they also found that the only documented indication for caesarean delivery in approximately half of these cases was maternal COVID-19, again suggesting that this effect may be iatrogenic in nature [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current state, obstetricians should maintain their obstetrical indications because contamination does not mean infection. Indeed, preventive measures during vaginal delivery, 4 reduced viral load exposure, and potential transplacental passage of antibodies from the mother to the fetus could reduce the risk of neonatal infection.…”
mentioning
confidence: 99%